Ergonomic optimization of airship passenger cabin design using RULA and fuzzy logic decision method - Aminian, Negin Ozve; Romli, Fairuz Izzuddin (The Aeronautical and Astronautical Society of the Republic of China, 2024)
This article addresses the design gap in the field of passenger transport airships by focusing on the internal cabin design. While the external structure of airships has received extensive attention, the internal cabins, specifically for the mass passenger transport, have not been adequately considered. The existing airship cabin designs have primarily catered to luxury and tourism, lacking the capacity to transport large quantities of people. To bridge this gap, this research aims to identify the key cabin factors and develop an ergonomic passenger seat using fuzzy logic method, with the specific focus on enhancing passenger comfort. The research work starts with the conduct of focus groups and expert interviews to establish the design requirements for the passenger cabin of a mass transport airship. Based on these requirements, an ergonomic passenger seat design is proposed, which is then assessed by RULA method to ensure passenger comfort is adequately addressed. In addition, fuzzy logic method is applied to optimize the overall passenger cabin design for the mass transport airship with the use of the proposed ergonomic passenger seat. The fuzzy logic process has been tailored to ensure the compliance with essential aviation regulation for mass passenger transport airships. The final optimized passenger cabin design for the mass passenger transport airship is presented. On the whole, the main contribution of this study lies in the construction of the membership functions and fuzzy rules, which have been verified by the industry experts within the airship domain. The findings not only reflect the current practices in the industry but also provide a generalized framework for airship internal cabin. In addition, based on the analysis results, the optimized cabin design can provide an adequate travel comfort for passengers of mass transport airships.